2015
DOI: 10.1002/ajh.24177
|View full text |Cite
|
Sign up to set email alerts
|

Polo‐like kinase and its inhibitors: Ready for the match to start?

Abstract: Polo-like kinases (Plks) plays a central role in the normal cell cycle and their upregulation has been shown to play a role in the pathogenesis of multiple human cancers. Preclinical work demonstrates that targeting Plk has a significant impact on the treatment of both solid and hematologic malignancies in vitro and in vivo. We review here the basic science and clinical work to date with the Plks as well as future directions with this novel class of mitotic inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 98 publications
0
13
0
Order By: Relevance
“…Our findings that Atm −/− ;Casp2 −/− lymphoma cells are more resistant to PLK1-I-mediated cell death may have important implications for drug resistance in lymphoma treatment. 47 It is important to note that, while in most dividing cells caspase-2 is inactive, 36 our findings demonstrate that following mitotic stress, a small population of Casp2 −/− cells are resistant to apoptosis and survive as multinucleate and aneuploid cells. Importantly, these cells acquire an ability to survive long term in culture, an attribute likely to contribute to enhanced cellular transformation and tumorigenic potential.…”
Section: Discussionmentioning
confidence: 68%
“…Our findings that Atm −/− ;Casp2 −/− lymphoma cells are more resistant to PLK1-I-mediated cell death may have important implications for drug resistance in lymphoma treatment. 47 It is important to note that, while in most dividing cells caspase-2 is inactive, 36 our findings demonstrate that following mitotic stress, a small population of Casp2 −/− cells are resistant to apoptosis and survive as multinucleate and aneuploid cells. Importantly, these cells acquire an ability to survive long term in culture, an attribute likely to contribute to enhanced cellular transformation and tumorigenic potential.…”
Section: Discussionmentioning
confidence: 68%
“…Monotreatment phase I/II trials showed limited partial response and stable disease with reduced adverse effects (summary from ref. 73). Subsequent phase I and II trials with combination treatments (such as cisplatin and cytarabine) show improvements in efficacies of response and overall survival for those who responded 85.…”
Section: Plk1 Inhibitors: Role In Chemoradiotherapymentioning
confidence: 99%
“…Multiple phase I/II trials show positive outcomes with partial responses in a few patients and stable disease in several patients (summary from ref. 73). Phase III trial is currently ongoing in patients with myelodysplastic syndrome.…”
Section: Plk1 Inhibitors: Role In Chemoradiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of PLK1 is variable in both normal and tumour tissues. This had therefore led to the massive development of PLK1 inhibitors, trying to target the PLK1 to improve the treatment outcomes [4] [5] [6] [7]. The development of the drugs was however often halted at Phase I trials, due to inconsistent outcomes and the massive side effects.…”
Section: Introductionmentioning
confidence: 99%